The nomenclatural types of four names in Lonicera (Caprifoliaceae) - Ferrer-Gallego, Pedro Pablo; Laguna, Emilio (Phytotaxa, 2018)
The nomenclatural types of Lonicera implexa, L. implexa var. longifolia, L. maialis and L. valentina are discussed. L. implexa was described from cultivated plants in the Royal Botanic Gardens at Kew, and it is neotypified using a specimen preserved at BM. The names L. maialis, currently included as a synonym of L. implexa var. valentina, and L. implexa var. longifolia are lectotypified from specimens preserved at BC and PAL herbaria, respectively. The protologue of the name L. valentina included a gathering that comprises only one specimen preserved at MA, and therefore it is considered as the holotype. This plant is currently accepted as a variety of L. implexa.